Initial growth of Calendula officinalis L. plants treated with paclobutrazol - Pedroza Cruz, Renata Ranielly; Ribeiro Pires, Ricardo; da Silva Guimarães, Maria Eduarda; Gomes Dias, Marlon; Mota Pereira, Ariana; Iarley da Silva, Toshik; Souto Ribeiro, Wellington; Saraiva Grossi, José Antonio (Comunicata Scientiae, 2022)
Calendula officinalis L. is largely used in composition in beds and like cutted flowers. On the other hand, the height (30 – 60 cm), difficult the cultivate and sales like potted plant, owing to the tipping of pots and for the disposition of plants on the tables. Paclobutrazol (PBZ) is a vegetal regulator that reduces the growth of plants. The purpose of this study was to evaluate the initial growth of C. officinalis L. treated with PBZ. The experiment was conducted in a greenhouse in the Floriculture Sector, of Agronomy Department, of Universidade Federal de Viçosa in October a November of 2020. The experiment was conducted in complety randomized desing and treatments were control, 2500, 5000, 7500 e 10000 ppm of PBZ doses with five repetitions. Two applications of PBZ doses were realized, being the first 15 days and the second 30 days after transplantation. Plant height, leaf area, stem length and diameter, root length, leaves number and photosynthetic pigments were quantified. PBZ, regardless of concentration, reduced plant heigth, leaf area, stem length, and diameter. Root length, leaves number and photossyntetic pigments did not significant among doses aplied. The initial growth of C. officinalis L. was reduced with PBZ doses.